Jonathan Huddleston, Eschatology in Genesis (FAT 2. Reihe 57; Tubingen: Mohr Siebeck 2012) - Lemański, Janusz (The Biblical Annals, 2016)
Book review: Jonathan Huddleston, Eschatology in Genesis (FAT 2. Reihe 57; Tubingen: Mohr Siebeck 2012). Pp. 315. € 69,00. ISBN 978-3-16-151983-3.